Spinal interventions in pain management - Simpson, Karen H.; Baranidharan, Ganesan; Gupta, Sanjeeva ([Oxford] : Oxford University Press, 2012)
Concentrating on techniques rather than pain pathology, this practical handbook is focused purely on the spine. The text covers anatomy and imaging, how to choose patients, how to undertake procedures, and includes advice on potential pitfalls.
Previously issued in print: 2012.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 18, 2016).
Keywords: Pain -- Treatment; Spine